Application of HPLC-Q/orbitrap MS in the detection and identification of anticancer constituents in ethyl acetate components from Hedyotis diffusa. Issue 32 (4th August 2020) - Chen, Xi; Zhao, Baojin; Zhang, Mengjiao; Dong, Min; Li, Yunlan; Li, Qingshan
Abstract : A feasible analytical method based on HPLC-quadrupole/electrostatic field orbitrap high-resolution mass spectrometry (HPLC-Q/orbitrap MS) was established for the identification and characterization of anticancer constituents in ethyl acetate components from Hedyotis diffusa . Abstract : A feasible analytical method based on high performance liquid chromatography-quadrupole/electrostatic field orbitrap high-resolution mass spectrometry (HPLC-Q/orbitrap MS) has been established for the identification and characterization of anticancer constituents in ethyl acetate components from Hedyotis diffusa in our work. The mass spectrometer provided significant fragment information both in the full MS scan and data-dependent MS 2 modes. Sixty-two possible compounds were analyzed and identified from the above results. Of the above 62 compounds, 12 have good separation in the positive ion mode, and 27 compounds have good separation in the anion mode. Currently, 39 have been reported in the literature related to the chemical composition of the plant, while the other 23 of the 62 compounds have not been reported. Fifteen tentatively identified compounds were given detailed descriptions. Four representative compounds from the ethyl acetate extract among the fifteen were actually isolated in good yield with silica gel column chromatography. Meanwhile, their structures were unambiguously identified as scopoletin, vanillic acid, p -coumaric acid and E -6- O-p -coumaroyl scandoside methyl ester using 1 H NMR, 13 C NMR, IR and UV spectroscopy. The purity of the ethyl acetate extracts, the total flavonoids, from Hedyotis diffusa could reach 65.6%. The inhibitory effect on HepG-2 cells of the total flavonoids was up to 66.2 ± 2.7%. Amentoflavone, quercetin, naringenin, and rutin were selected from the total flavonoids. The amentoflavone and quercetin had better hepatoprotective activity. The inhibition rates of 500 μmol L −1 amentoflavone and quercetin on HepG-2 cells could reach 56.2 ± 8.1% and 78.0 ± 9.3%, respectively. The EtOAc extracts could induce apoptosis in HepG2 cells by blocking the cell cycle in the G0/G1 phase. To the best of our knowledge, this is the first time that Q-orbitrap HRMS was applied to detect potential anticancer compounds in Hedyotis diffusa . This analytical method proved to be a feasible approach for the rapid detection of the potential anticancer compounds from Hedyotis diffusa .